Exploring prevalence and risk factors association of osteoporosis among chronic obstructive pulmonary disease patients: a cross-sectional study in western Rajasthan - Kumar Soni, Laxman; Soni, Priyanka; Praveen Kumar Garg; Kaur, Daljeet; Aman Deep (International Journal Of Community Medicine And Public Health, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory condition with progressive respiratory symptoms and systemic complications, including osteoporosis. It is characterized by decreased bone mass represents significant health risks among COPD patients. However, associated risk factors were partially understood requires further exploration. Methods: Study conducted at a tertiary care hospital in western Rajasthan, India, we aimed to assess the prevalence and risk factors association of osteoporosis among COPD patients. A cross-sectional study was conducted from January 2023 to December 2023, involving 102 COPD patients by Convenience sampling categorized according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria. Bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry (DEXA), and demographic and clinical data were collected. Results: Our findings revealed high prevalence of osteoporosis (48%) among COPD patients, showed significant associations with advancing age, female sex, underweight status, and more severe COPD stages. Female gender, older age, underweight status, higher Modified Medical Research Council (mMRC) dyspnea scores, and advanced GOLD stages were identified as significant risk factors for osteoporosis. Conclusions: These results underscore the importance of early screening and management of osteoporosis in COPD patients to mitigate its adverse effects on quality of life and morbidity. Implementing routine BMD measurements using DEXA in COPD management protocols can facilitate timely diagnosis and intervention, ultimately improving patient outcomes. Further research is warranted to elucidate the mechanistic links between COPD and osteoporosis and to explore targeted therapeutic strategies for mitigating bone loss and fracture risk in this vulnerable population.